Installation of automated teller machine on-campus - De La Salle University, Manila (Animo Repository, 1990)
United Coconut Planters Bank installed on-campus automated teller machine which connects to MegaLink, a network of major ATMs. The machine, located on the north wing of La Salle Hall and one of the bank's only two off-site ATMs was inaugurated on this date.